Sobre Ludwigia hyssopifolia (G. Don) Exell (Onagraceae) como integrante de la flora subespontánea valenciana - Ferrer-Gallego, P. Pablo; Laguna Lumbreras, Emilio (Acta Botanica Malacitana, 2009)
Ludwigia hyssopifolia (G. Don) Exell (Onagraceae) a new species for the Valencian subspontaneous flora. Palabras clave. Ludwigia hyssopifolia, Onagraceae, corología, Valencia, Península Ibérica. Key words. Ludwigia hyssopifolia, Onagraceae, chorology, Valencian province, Iberian Peninsula.